Controlled atmosphere storage of fruits and vegetables - Thompson, A. K. [ (A. Keith)] (CABI Publishing, 2010)
The transportation and storage of fresh fruits and vegetables is an international operation where technology must be used to ensure that produce reaches the consumer in the best possible condition. This title presents a comprehensive overview of controlled and modified atmosphere storage